Exploring the Discriminant Validity of the Modified Arm Care Screen (MACS), Designed for Overhead Athletes, in Detecting Musculoskeletal Risk Factors in the General Population - Eleftherios Paraskevopoulos; Styliani Pentheroudaki; Maria Papandreou (Biomechanics)
Background: Shoulder pain is the third most common musculoskeletal issue in primary care, affecting up to 50% of patients six months post-consultation, leading to significant functional impairments and societal costs, especially due to sick leave. Shoulder injuries are particularly prevalent among ‘overhead athletes’ in sports like swimming, volleyball, and handball, with high injury rates reported annually. Screening tools like the Arm Care Screen (ACS) have been used to effectively identify athletes at risk of shoulder injuries. However, their applicability to the general population is less understood. This study aimed to assess the discriminant validity of a modified ACS (MACS) in detecting musculoskeletal risk factors among non-athletes. Methods: A prospective cross-sectional study was conducted with 30 asymptomatic subjects over 18, excluding those with a history of shoulder injuries or surgeries. The MACS, comprising four tests, was administered, and its diagnostic performance was evaluated through sensitivity, specificity, predictive values, and likelihood ratios. Results: The results indicated low sensitivity (0–47.62%) and variable specificity (55.56–100%), suggesting that the MACS may not effectively identify risk factors in the general population. Positive and negative predictive values were inconsistent (ranging from 0 to 100), as well as positive and negative likelihood ratios (ranging from 0 to 3.47), highlighting the need for non-athlete-specific screening tools. Conclusion: While the MACS shows promise in athletes, its application in the general population requires further refinement. This study underscores the necessity for tailored screening methods to enhance the early detection and prevention of musculoskeletal issues in diverse populations.